2014
DOI: 10.3390/rs6031803
|View full text |Cite
|
Sign up to set email alerts
|

Burned Area Detection and Burn Severity Assessment of a Heathland Fire in Belgium Using Airborne Imaging Spectroscopy (APEX)

Abstract: Uncontrolled, large fires are a major threat to the biodiversity of protected heath landscapes. The severity of the fire is an important factor influencing vegetation recovery. We used airborne imaging spectroscopy data from the Airborne Prism Experiment (APEX) sensor to: (1) investigate which spectral regions and spectral indices perform best in discriminating burned from unburned areas; and (2) assess the burn severity of a recent fire in the Kalmthoutse Heide, a heathland area in Belgium. A separability ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
68
2
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(100 citation statements)
references
References 76 publications
(183 reference statements)
9
68
2
5
Order By: Relevance
“…Among them, MIRBI, BAI, and Greenness are the best when averaging all vegetation types, while NDVI and NBR get better scores in isolated vegetation types. Other studies obtained similar results, e.g., better discrimination capabilities of BAI [18,22,28], Greenness [24,62], or MIRBI in shrub-savannah ecosystems [25,27,52]. Although NBR is often considered the best SI for burned area mapping short time after fire and therefore widely used for burn severity assessments [7,19,21,23,[27][28][29], our results demonstrated that in certain vegetation types other SI would offer a better option.…”
Section: Summary Of Results Which Si Should We Choose?supporting
confidence: 78%
See 2 more Smart Citations
“…Among them, MIRBI, BAI, and Greenness are the best when averaging all vegetation types, while NDVI and NBR get better scores in isolated vegetation types. Other studies obtained similar results, e.g., better discrimination capabilities of BAI [18,22,28], Greenness [24,62], or MIRBI in shrub-savannah ecosystems [25,27,52]. Although NBR is often considered the best SI for burned area mapping short time after fire and therefore widely used for burn severity assessments [7,19,21,23,[27][28][29], our results demonstrated that in certain vegetation types other SI would offer a better option.…”
Section: Summary Of Results Which Si Should We Choose?supporting
confidence: 78%
“…Initially designed for burned area extraction, NBR is the most popular spectral index used for burn severity assessments with different sensors in several ecosystems around the world. In numerous comparative analyses, NBR proved to be one of the most efficient SI [14,19,21,23,28]. In time series analyses, NBR showed good correlations with field-based composite burn index scores several years after a fire, thus representing an efficient tool for vegetation recovery monitoring [29,30].…”
Section: Index Full Name Abbreviation Equation Referencementioning
confidence: 94%
See 1 more Smart Citation
“…NDVI is a commonly used index for post-fire vegetation response in the literature [2,33,43] and is based on the absorption and reflection characteristics of plants in the red and near-infrared spectral regions [12]. In addition to NDVI, previous work [44] has proposed the use of the Normalized Burn Ratio (NBR) [26], and the differenced Normalized Burn Ratio (dNBR) [26] for detecting and monitoring post-fire vegetation changes over time.…”
Section: Satellite Datamentioning
confidence: 99%
“…First, we computed the mean value of each spectral band (i.e., blue, green, red, near-infrared). Then, since various studies have shown that the variation of the vegetation cover after a severe fire event is highly correlated with the magnitude of the burn severity [12,33,41] we computed the mean Normalized Difference Vegetation Index (NDVI) [42] per sampling plot. We applied the same procedure to both post-fire images (i.e., GeoEye time1 and GeoEye time2 ).…”
Section: Satellite Datamentioning
confidence: 99%